Determination of poverty among the poor and needy in a developing country / Ahmad Fahme Mohd Ali and Mohd Faisol Ibrahim. - Mohd Ali, Ahmad Fahme; Ibrahim, Mohd Faisol (Universiti Teknologi MARA Selangor, 2018)
This article attempts to analyse the determination of poverty among the poor and needy of the zakat recipients in Kelantan, Malaysia. The study is motivated from the Kelantan zakat collection (2003-2015) that suggests that the growth alone (high collection) is not enough to eliminate poverty, there are indeed, other elements of poverty eradication like the socio economic, demographic factors, remittances and the investments in social and economic factors like the food subsidy for the poorest, good quality education, opportunities for the most needy, regulation of job markets, and purposively designed social security nets also have significant impact on permanent reduction in poverty. In Kelantan, despite zakat centres having disbursed an increasing amount of expenditure annually on the two categories of zakat recipients, hitherto the number of fuqara (poor) and masakin (needy) households is still increasing (MAIK, 2014; JAWHAR, 2012). Thus, it is important to understand the nature and scale of poverty, the various driving forces that affect it and the determinants of poverty among the poor and needy as linked to this process. A sample of 505 households from 2016 Household Expenditure Survey (HES) among the poor and needy zakat recipients in Kelantan has been used in this study. The findings have important policy implications for Kelantan Zakat Department (MAIK) in making the zakat distribution becomes more efficient and uplift the important role of zakat as one of the poverty alleviation tools among the Muslims. This study recommends the method of zakat distribution should be improved and channelled accordingly in order to strengthen the Muslims economy condition and then, it would facilitate the poverty alleviation programmes by the zakat department.